Influence of walking on knee ligament response in car-to-pedestrian collisions - Chen, Wentao; Tang, Jisi; Shen, Wenxuan; Zhou, Qing (Frontiers in Bioengineering and Biotechnology, 2023)
Pedestrians are likely to experience walking before accidents. The walking process imposes cyclic loading on knee ligaments and increases knee joint temperature. Both cyclic loading and temperature changes affect ligament material properties, which further influence injury risk. However, the effect of such walking-induced material property changes on pedestrian ligament response has yet to be considered. Therefore, in this study, we investigated the influence of walking on ligament response in car-to-pedestrian collisions. Using Total Human Model for Safety (THUMS) model, knee ligament responses (i.e., cross-sectional force and local strain) were evaluated under several crash scenarios (i.e., two impact speeds, two knee contact heights, and three pedestrian postures). In worst case scenarios, walking-induced changes in ligament material properties led to a 10% difference in maximum local strain and a 6% difference in maximum cross-sectional force. If further considering the material uncertainty caused by experimental dispersion, the ligament material property changes due to walking could result in a 28% difference in maximum local strain and a 26% difference in maximum cross-sectional force. This study demonstrates the importance of accounting for walking-induced material property changes to quantify the uncertainty and reliability of safety assessments and injury analysis.